Clinical and Postoperative Outcomes of Laparoscopic versus Open Inguinal Hernia Repair at Rajshahi Medical College Hospital - Md Shohidul Islam; Habibun Nobi Md Shafiquzzaman; Salma Akter (TAJ: Journal of Teachers Association, 2026)
Background: Inguinal hernia is one of the most common surgical conditions, and both open and laparoscopic mesh repair are widely practiced. Although open repair remains common in many hospitals, laparoscopic repair may offer advantages in terms of postoperative pain, recovery, and patient satisfaction. Methods: This hospital-based comparative study included 100 patients who underwent inguinal hernia repair. Patients were equally divided into two groups: 50 underwent laparoscopic repair and 50 underwent open repair. Baseline characteristics, clinical profile, operative outcomes, postoperative pain, analgesic requirement, early recovery, complications, chronic groin pain, return to normal activity and work, patient satisfaction, and recurrence were compared between the two groups. Results: The laparoscopic group had significantly lower postoperative pain scores at 6 hours, 24 hours, 48 hours, discharge, and follow-up visits compared with the open group. Analgesic requirement was lower in the laparoscopic group. Time to oral feeding, time to mobilization, postoperative hospital stays, return to normal activity, and return to work were also significantly shorter after laparoscopic repair. Postoperative complications, including wound infection, hematoma, scrotal swelling, urinary retention, postoperative fever, and mesh infection, were more frequent in the open repair group. Chronic groin pain at 3 months was lower in the laparoscopic group. Patient satisfaction was higher after laparoscopic repair. Recurrence was rare and did not differ significantly between the two groups. Conclusion: Laparoscopic inguinal hernia repair was associated with lower postoperative pain, reduced analgesic requirement, faster recovery, fewer early complications, lower chronic groin pain, and higher patient satisfaction compared with open repair. However, baseline differences between groups should be considered when interpreting the findings.